The Assessment of Internal Control System in Management of Information Technology Based on COSO IC - Muhammad Fadlan; Wing Wahyu Winarno; Kholid Haryono; Muhammad - (SENATIK STT Adisutjipto, 2018)
The large number of institutions that use information technology (IT) to help run their usiness processes cannot be separated from various risks to IT. The internal control system is one way that can be used to deal with and even minimize the impact of various risks and COSO Internal Control is one of the frameworks that can be used. The "XYZ" College is one of the educational institutions that have used IT, especially to assist every activity related to students. At present, there are no assessments related to the internal control system in the utilization and management of IT contained in the institution, so it is not known whether the control system is running well or not. For this reason, this study was conducted with the aim of assessing whether the internal control system is currently in accordance with the principles of good internal control based on the COSO Internal Control Framework. The results showed that indirectly the "XYZ" College had applied several principles contained in the COSO Internal Control, even being quite good with a value of 3.28 from a scale of 5.0.